The causal effects of education on health outcomes in the UK Biobank. (February 2018) - Davies, Neil; Dickson, Matt; Davey Smith, George; van den Berg, Gerard; Windmeijer, Frank
Abstract Educated people are generally healthier, have fewer comorbidities and live longer than people with less education1–3 . Much of the evidence about the effects of education comes from observational studies, which can be affected by residual confounding. Natural experiments, such as laws that increase the minimum school leaving age, are a potentially more robust source of evidence about the causal effects of education. Previous studies have exploited this natural experiment using population-level administrative data to investigate mortality, and surveys to investigate the effect on morbidity1, 2, 4 . Here, we add to the evidence using data from a large sample from the UK Biobank5 . We exploit the raising of the minimum school leaving age in the UK in September 1972 as a natural experiment6 . We used a regression discontinuity design to investigate the causal effects of remaining in school. We found consistent evidence that remaining in school causally reduced the risk of diabetes and mortality in all specifications. The authors exploit a 1972 policy that increased the minimum school leaving age to investigate the causal effects of staying in school on health. Using a large dataset, they find that remaining in school reduces the risk of diabetes and mortality.